Prinsip Terapi Cairan dan Elektrolit pada Ketoasidosis Diabetikum Anak - Gusti Ayu Amalindasari Prabayastita Masta (Cermin Dunia Kedokteran, 2024)
Diabetic ketoacidosis (DKA) is a complication in type 1 diabetes pediatric patients with quite high morbidity and mortality rates. The basic treatment in pediatric DKA is fluid and electrolyte correction. Hydration can reduce counterregulatory hormones, increase renal glucose clearance, and increase insulin sensitivity. The purpose of administering fluids is to fill intravascular, interstitial and intracellular fluids. There is still debate regarding the risks of cerebral edema or even pulmonary edema.